A Clinical Study to Evaluate Efficacy of KVGAP’S Femicare Syrup on Raktapradara w.s.r to Dysfunctional Uterine Bleeding (International Journal of Ayurveda and Pharma Research, 2022)
Dysfunctional uterine bleeding (Raktapradara) is the commonest gynaecological disorder affecting the quality women’s life of reproductive age group. A clinical study was conducted with KVGAP’S Femicare Syrup on 28 patients of DUB. KVGAP’S Femicare syrup is a polyherbal Ayurvedic formulation prepared from ingredients like Ashoka, Ashwagandha, Gokshura, Guduchi, Shatavari, Manjhistha, Usheera, Kumari, Sariva, Pippali, and Shilajathu. The parameters assessed were number of bleeding episodes, excessive bleeding, investigators global assessment scale, VAS for pain, participants overall assessment scale, clot and interval (number of days of the cycle). Patients were assessed at the beginning of the trail, after 1 month and after 2 months. 56.52%, 73.08%, 77.6%, 85%, 81.93%, 100% improvement were observed in the clinical parameters assessed (number of bleeding episodes, excessive bleeding, investigators global assessment scale, VAS for pain, participants overall assessment scale, clot) respectively. Results were statistically significant. Interval didn’t show any changes. Out of 28 patients in this study, 1 patient shown mild improvement, 11 patients (39%) were shown moderate improvement and 16 patients (57%) had marked improvement. Overall effect of the treatment was 77.31%. This study showed that KVGAP’S Femicare syrup showed promising results in treating DUB. Hence it can be concluded that KVGAP’S Femicare Syrup is effective and safe in the management of dysfunctional uterine bleeding.